Vitamin D and Lupus: Are we doing enough? - Neha V. Chiruvolu; Yasaman Safarpour; Vaneet K. Sandhu (Greater Baltimore Medical Center, 2021)
The aim of this study is to identify rheumatology practice care gaps in evaluating for vitamin D deficiency in systemic lupus erythematosus (SLE), as well as adherence to vitamin D replacement in SLE patients currently on corticosteroid therapy. Data for this study were collected from the Southern California Lupus Registry in addition to data extraction from medical health records. Evaluation of serum vitamin D level within 6 months of patient encounter, current or prior use of systemic corticosteroids, and vitamin D replacement in patients receiving corticosteroid therapy were noted. Vitamin D deficiency was defined as serum 25(OH)D3 less than 30 ng/ml. Of 182 patients in the cohort, data were available for 176. Evaluation of vitamin D deficiency was noted in 49 patients (28%), 27 (55%) of whom had abnormal values. Current corticosteroid use was noted in 56 (32%) patients and prior use in 73 (41%). Vitamin D replacement was prescribed to 30 (54%) patients with current corticosteroid use. In an academic rheumatology clinic, we have identified underevaluation for vitamin D deficiency in SLE patients despite increasing awareness of its contribution to disease activity. Further, routine supplementation of vitamin D is particularly lacking in individuals receiving systemic corticosteroids. This presents a practical opportunity for improvement in SLE clinical care.